Structural Iron (II) of Basaltic Glass as an Energy Source for Zetaproteobacteria in an Abyssal Plain Environment, Off the Mid Atlantic Ridge - Henri, Pauline A.; Rommevaux-Jestin, Céline; Lesongeur, Françoise; Mumford, Adam; Emerson, David; Godfroy, Anne; Ménez, Bénédicte (Frontiers in Microbiology, 2016)
To explore the capability of basaltic glass to support the growth of chemosynthetic microorganisms, complementary in situ and in vitro colonization experiments were performed. Microbial colonizers containing synthetic tholeitic basaltic glasses, either enriched in reduced or oxidized iron, were deployed off-axis from the Mid Atlantic Ridge on surface sediments of the abyssal plain (35°N; 29°W). In situ microbial colonization was assessed by sequencing of the 16S rRNA gene and basaltic glass alteration was characterized using Scanning Electron Microscopy, micro-X-ray Absorption Near Edge Structure at the Fe-K-edge and Raman microspectroscopy. The colonized surface of the reduced basaltic glass was covered by a rind of alteration made of iron-oxides trapped in a palagonite-like structure with thicknesses up to 150 μm. The relative abundance of the associated microbial community was dominated (39% of all reads) by a single operational taxonomic unit (OTU) that shared 92% identity with the iron-oxidizer Mariprofundus ferrooxydans PV-1. Conversely, the oxidized basaltic glass showed the absence of iron-oxides enriched surface deposits and correspondingly there was a lack of known iron-oxidizing bacteria in the inventoried diversity. In vitro, a similar reduced basaltic glass was incubated in artificial seawater with a pure culture of the iron-oxidizing M. ferrooxydans DIS-1 for 2 weeks, without any additional nutrients or minerals. Confocal Laser Scanning Microscopy revealed that the glass surface was covered by twisted stalks characteristic of this iron-oxidizing Zetaproteobacteria. This result supported findings of the in situ experiments indicating that the Fe(II) present in the basalt was the energy source for the growth of representatives of Zetaproteobacteria in both the abyssal plain and the in vitro experiment. In accordance, the surface alteration rind observed on the reduced basaltic glass incubated in situ could at least partly result from their activity.